Determinants and stability of dividend payment: the case of Malaysian public-listed Shariah-compliant firms - Fauzias Mat Nor,; Nur Ainna Ramli,; Ainulashikin Marzuki,; Norfhadzilahwati Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper was to examine the determinants and stability of dividend payments in Malaysia from 2007 to 2016. The purposes of this research were (1) to analyse the stability of dividend per share, (2) to examine the determinants of dividend yield, and (3) to examine the effect of dividend per share on the sustainable growth rate of Shariah-compliant firms in Malaysia. Static model and dynamic model estimated using Generalised Method of Moment were used in this research. The results indicated that the stable earnings per share can afford the firms to pay a larger dividend. Futhermore, the higher dividend from the previous year with the lower speed adjustment indicated high smoothing and stability of dividend payment. The results on determinants of the dividend yield revealed the five factors that are lagged dividend yield, firm size, sales growth, leverage, and market value to book value have a significant impact on dividend yield, with lagged dividend yield and firm size showing a significant positive effect, while sales growth, leverage, and market value to book value have a significant negative impact. In addition, the results indicated that dividend per share had a significantly positive impact on the sustainable growth rate. The results of this study are important for the management team of companies to decide an appropriate dividend policy for the company to maintain a stable dividend payment and have the financial health of a company, These results also provided the understanding of dividend policy behaviour in Malaysia, particularly on Malaysian public-listed Shariah-compliant firms.